(untitled) (Applied Biological Research, 2024)
The aim of the study was to examine the toxic effect of sulphur dioxide on the ovaries of female rats. The effect of different concentrations of SO2 (0, 5, 10 and 15 ppm) on antioxidant enzymes and histopathological changes were investigated in ovaries of female rats under natural and experimental conditions. Naturally exposed, house rats, Rattus rattus (Group I) were collected from agricultural fields alongside the road in Ludhiana, India and acclimatized for 1 month in laboratory. Laboratory-bred house rats were divided into four groups. Group II (control rats), III, IV and V were first exposed to the filtered air in 1 m3 exposure chamber for 5 h day-1for 28 days and then treated with 0, 5, 10 and 15 ppm of SO2, respectively. SO2 treatment showed significant increase in lipid peroxidation (LPO) levels, followed by significant decrease in the activities of superoxide dismutase (SOD), catalase (CAT), glutathione reductase (GR), glutathione-S-transferase (GST) and GSH-PX in ovaries of female rats. The results revealed that SO2 can cause oxidative damage to the ovaries of female rats. The increase in LPO and decrease in other enzymes was more prominent at higher SO2 concentration as compared to the other tested concentrations.